PENINGKATAN HASIL BELAJAR TEMA 7 DAN 8 MELALUI VIDEO PEMBELAJARAN BERBASIS TPACK (Penelitian Tindakan Kelas Pada Siswa Kelas IVA SDN Cadasari 3 Kecamatan Cadasari Kabupaten Pandeglang Tahun 2021) - Ratu Dina Maria Herviani (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2021)
The purpose of this research is to improve the application and learning outcomes of students on Themes 7 and 8 in class IVA SDN Cadasari 3 District Cadasari Pandeglang Regency. The method used in this study is Class Action Research with 3 cycles. Data collection tools in the form of evaluation test questions, teacher activity observation sheets, and student activities. Data processing is done by calculating the average results of evaluation tests, average observation results of teacher activity, and average student activity. The results of these calculations are used to determine the improvement of students' learning outcomes by using TPACK-based learning video media. The improvement of student learning outcomes in aspects of attitude, knowledge and skills in each cycle is as follows: cycle I grades the average student learning outcome is 66.63 with learning completion of 43.17%, cycle II the average value of student learning outcomes is 75.83 with a completion of 71.58%, while in cycle III the average score of student learning outcomes is 87.00 with a completion of 100% The application of learning video media to the activities of students and teachers is increasing. Based on the results of the analysis, it can be concluded that by using TPACK-based learning video media learning outcomes on themes 7 and 8 can be improved.